ANALISIS ALIH KODE PADA FILM BADARAWUHI DI DESA PENARI KARYA SUTRADARA KIMO STAMBOEL: KAJIAN SOSIOLINGUISTIK - Ariyana Rahmawati, Ariyana Rahmawati (Jurnal Lazuardi, 2025)
This study aims to analyze the use of language in Kimo Stamboel's film "Badarawuhi di Desa Penari" through a sociolinguistic study, with a primary focus on the phenomenon of code switching. By applying a qualitative approach and library research techniques, this study collected data from dialogues in the film and references to related sources. The analysis was conducted using the listening and note-taking method, followed by data processing through qualitative descriptions. The findings of this study reveal two types of code switching: internal code switching and external code switching. Internal code switching occurs when speakers switch between Indonesian and Javanese within the framework of the national language, which is usually triggered by situational conditions, social relationships, and closeness between characters. External code switching occurs when speakers switch from Indonesian to Arabic, especially in religious contexts such as basmalah, hamdalah, salam, and belasongkondolence. This phenomenon shows that code switching is not merely a means of communication, but also reflects the cultural identity, religious values, and social rules of the society depicted in the film. In general, the results of this study confirm that the film "Badarawuhi di Desa Penari" depicts the social reality of Javanese society through the use of authentic, contextual, and culturally rich language. This research is expected to contribute to the advancement of sociolinguistic studies, particularly in understanding the application of language in audiovisual works, as well as being a reference material for researchers, academics, and practitioners in the fields of language and film. Keywords: Sociolinguistic Study, Code Switching, Badarawuhi Film in Penari Village